2007
DOI: 10.1016/j.aorn.2007.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Standing in the OR: A Dutch Research Study

Abstract: Prolonged standing is considered to be an occupational risk factor for musculoskeletal disorders. This cross-sectional, multicenter study examined whether Dutch perioperative personnel exceeded ergonomic guidelines for standing in the workplace (ie, not more than one hour of continuous standing and not more than four hours of standing in total per day). Perioperative personnel in 16 hospitals recorded their standing times on a daily basis. The average standing time in the OR was 2.5 hours per work day; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 6 publications
2
22
0
5
Order By: Relevance
“…Musculoskeletal symptoms associated factors a) Perceived physical demands Statistical analysis of the data, similar to the other studies findings [28][29][30][31] , showed that perceived physical demands i.e., pulling/pushing heavy objects, moving/lifting/lowering heavy loads, repetitive motions with hands/wrists and bent or twisted posture of the trunk, were significantly associated with musculoskeletal symptoms in different body regions. In accordance with Addington's results 28) , there was no relationship between lifting or lowering and low back problem, while bending and twisting at the waist had association.…”
Section: Discussionsupporting
confidence: 63%
“…Musculoskeletal symptoms associated factors a) Perceived physical demands Statistical analysis of the data, similar to the other studies findings [28][29][30][31] , showed that perceived physical demands i.e., pulling/pushing heavy objects, moving/lifting/lowering heavy loads, repetitive motions with hands/wrists and bent or twisted posture of the trunk, were significantly associated with musculoskeletal symptoms in different body regions. In accordance with Addington's results 28) , there was no relationship between lifting or lowering and low back problem, while bending and twisting at the waist had association.…”
Section: Discussionsupporting
confidence: 63%
“…Long standing for more than four hours was reported in more than 45% of the current studied sample (Table 4), which oppose the ergonomic guidelines for standing that should not exceed one hour of incessant standing and four hours in total per day (Meijsen and Knibbe, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative changes of the meniscus reduce its ability to distribute weight-bearing forces 26) . Prolonged standing leads to continuous concentrated compression on small, load-bearing regions of the knee cartilage, which may result in local disruptions to the blood supply as well as wear and tear on the cartilage 27) . Thus, one interpretation of the present findings could be that the adverse effect of standing or walking on the knee cartilage is more pronounced with the degeneration of the meniscus.…”
Section: Individual Factorsmentioning
confidence: 99%
“…Sustained muscle activity has been previously reported as a risk factor for developing musculoskeletal symptoms 8) . Also, standing and walking for long periods of time leads to continuous load-bearing of the joints of the lower extremity, which may result in joint injury 27) . Thus, it is plausible that a long work-day or continuously working without a day-off may lead to an accumulation of musculoskeletal overload and/or insufficient time for the natural healing process of an injured structure, resulting in the development of musculoskeletal disorders 33) .…”
Section: Work-related Physical Factorsmentioning
confidence: 99%